2016
DOI: 10.4236/health.2016.814145
|View full text |Cite
|
Sign up to set email alerts
|

Brief Screening Tools for Long-Term Sickness Absence Due to Mental Disorders in Public Servants

Abstract: BACKGROUND: Mental disorders are often a cause of long-term sickness absence (LTSA). Kessler 6 (K6) and the Brief Job Stress Questionnaire (BJSQ) are short mental health assessment questionnaires and widely used for assessing mental health in the workplace. OBJECTIVE: The purpose of this study is to evaluate the screening performance of these tools for the prediction of LTSA due to mental disorders (LTSA-MD). METHODS: K6 and BJSQ were administered to 19,321 public servants, of whom 131 took LTSA-MD during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A previous study reported that high levels of stress response have a significant relationship with the onset of depression among Japanese employees in a software company 16 ) . Our earlier study showed that the BJSQ scale of stress response can effectively predict the occurrence of workers with LTSA-MD 17 ) . Furthermore, the NIOSH job stress model proposes that stress reactions are affected by job stressors 18 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that high levels of stress response have a significant relationship with the onset of depression among Japanese employees in a software company 16 ) . Our earlier study showed that the BJSQ scale of stress response can effectively predict the occurrence of workers with LTSA-MD 17 ) . Furthermore, the NIOSH job stress model proposes that stress reactions are affected by job stressors 18 ) .…”
Section: Discussionmentioning
confidence: 99%